Epistemic robustness of sets closed under rational behavior - Geir Asheim; Mark Voorneveld; Jörgen W. Weibull (Stockholm School of Economics, The Economic Research Institute (EFI), 2009)
This paper provides two conditions of epistemic robustness, robustness to alternative best replies and robustness to non-best replies, and uses them to characterize variants of curb sets in finite games, including the set of rationalizable strategies.
Keywords: C72; D83; 330; epistemic game theory; epistemic robustness; rationalizability; closedness under rational behavior; mutual p-belief; Rationales Verhalten; Spieltheorie; Nichtkooperatives Spiel; Robustes Verfahren; Theorie